Finite Element Modeling Application in Forensic Practice: A Periprosthetic Femoral Fracture Case Study - Terzini, Mara; Aldieri, Alessandra; Nurisso, Stefania; De Nisco, Giuseppe; Bignardi, Cristina (Frontiers in Bioengineering and Biotechnology, 2020)
The incidence of periprosthetic fractures has rapidly increased in the last two decades and has been the cause of a large number of revision surgeries and permanent physical disability for many patients, as well as a significant socioeconomic burden for many nations. This research deals with a periprosthetic femur fracture real event, occurred following a total hip arthroplasty and treated with one of the most widespread internal fixation methods: the implant of a periprosthetic femur plate system. A Finite Element analysis was performed to investigate the implanted femur plate break after a short follow-up and to understand the plate break causes. Such events are currently object of forensic debate as more and more often hospitals, surgeons and medical device manufacturers are denounced by patients to whom similar events occur. In this work, different load situations acting on the femur during daily and incidental activities were simulated, in order to validate the correct behaviour of the plate, according to the intended use recommended by the manufacturer. The analysis demonstrates that the plate failure can occur in situations of unconventional loading such as that caused by stumbling and in presence of incomplete bone healing.